PENGARUH KLAIM TERHADAP SURPLUS-DEFISIT UNDERWRITING PERUSAHAAN ASURANSI UMUM SYARIAH DI INDONESIA (Studi Pada Perusahaan Asuransi Umum Syariah yang Terdaftar di Otoritas Jasa Keuangan Periode 2015-2018) - Rustamunadi Rustamunadi; Suwaibah Suwaibah (UIN Sultan Maulana Hasanuddin Banten, 2020)
An increasingly developed economy and technology will lead to the possibility of risk, which threatens the growing human needs. Under these circumstances, the greater the problems that will be faced by humans, both directly and indirectly. From the financial data contained in the table, it can be seen that the claims and Surplus-Deficit Underwriting of Sharia General Insurance Companies in Indonesia from 2015 to 2018 have experienced significant developments fluctuations. This study was conducted to examine how much influence the claim has on the Surplus-Deficit Underwriting of Sharia General Insurance Companies in Indonesia with the object of research being Sharia General Insurance Companies and Sharia Units registered at the Financial Services Authority (OJK). The samples used were 8 Sharia General Insurance Companies and Sharia Units that met the sample criteria. The observation period of this research is from 2015 to 2018. The method used in this study is a quantitative method that uses the classic assumption test, hypothesis test, and the coefficient of determination test. The data used is secondary data obtained from the official website of Islamic insurance companies in Indonesia. The analysis tool in this study uses simple regression analysis that involves one independent variable as a predictor of the value of the dependent variable. The statistical analysis used was software namely SPSS Version 16.0. The results of this study indicate that the claim has a significant positive effect on Surplus-deficit Underwriting, this can be seen from the value of tinag amounted to 4,401 while the value of ttable obtained from the distribution table was sought at the significance of 5% degrees of freedom (df) n-k-l or 32-1-1 = 30 then obtained a ttable of 2.045. Therefore tinag> ttable = 4401 > 2,045 and significant level 0.000, because the significance value is less than 0.05, it can be concluded that H0 is rejected and Ha is accepted. The relationship between Claims Underwriting Surplus-Deficit is categorized as medium and the magnitude of the influence of Claims on Underwriting Surplus-Deficit is 43.7% while the rest is influenced by other variables not discussed in this study. The hypothesis proposed in this study is that H0 was rejected and Ha was accepted. This means that the claim has a significant positive effect on the surplus-deficit underwriting.